The influence of diapirism and deglaciation on the development of the neoproterozoic stratigraphy of the Amadeus Basin, Central Australia - Kennedy, Martin J. (Martin John) (1993)
Clarifies the relationship between controversial stratigraphic relations within the Neoproterozoic section by identifying locally dominant processes. Identification of these processes refine currently existing models of stratigraphic development and provide a basis for separating them from tectonic influences on a craton scale.